Product Innovation of Foodpreneurs Towards Customer Loyalty - Garcia, Alessandro Daeli; Rosyid, Adhe Muhammad; Yusup, Muhamad; Khasanah, Miftakhul (Pandawan Sejahtera Indonesia, 2025)
This study examines the relationship between product innovation and customer loyalty in the foodpreneur industry. In an increasingly competitive market, businesses must continuously innovate to maintain consumer interest, differentiate their brand, and enhance customer engagement. This research aims to assess the impact of product innovation on customer loyalty, with customer satisfaction as a mediating factor. This study employs a Systematic Literature Review (SLR) method by analyzing 20 journal articles published between 2021 and 2025. The articles were selected based on their relevance to product innovation, customer loyalty, and customer satisfaction in the foodpreneur sector. The findings indicate a strong positive relationship between product innovation and customer loyalty, with customer satisfaction serving as a crucial mediator. Satisfied customers are more likely to make repeat purchases and recommend brands, strengthening longterm loyalty. Additionally, product quality and market orientation significantly contribute to customer retention. Businesses that integrate consumer feedback, maintain high product standards, and prioritize innovation are more likely to build strong customer loyalty. This study suggests further exploration of the impact of digital transformation, technological advancements, and changing consumer behavior on product innovation. Furthermore, the role of social media engagement and influencer marketing could provide valuable insights into enhancing brand visibility and consumer trust.